Professional Android, 4th Edition - Meier, Reto; Lake, Ian (Wrox, 2018)
The comprehensive developer guide to the latest Android features and capabilities Professional Android, 4th Edition shows developers how to leverage the latest features of Android to create robust and compelling mobile apps. This hands-on approach provides in-depth coverage through a series of projects, each introducing a new Android platform feature and highlighting the techniques and best practices that exploit its utmost functionality. The exercises begin simply, and gradually build into advanced Android development. Clear, concise examples show you how to quickly construct real-world mobile applications. This book is your guide to smart, efficient, effective Android development. Learn the best practices that get more out of Android Understand the anatomy, lifecycle, and UI metaphor of Android apps Design for all mobile platforms, including tablets Utilize both the Android framework and Google Play services.